CCL17 and CCL22 induce CCR4 receptor expression and promote cytokine-induced killer cells migration. Issue 2 (February 2022) - Dong, Yongjian; Gao, Shuhui; Zhang, Xuefang; Kou, Jing; Liu, Jing; Ye, Ting; Shen, Han
Abstract : Recently, cytokine-induced killer (CIK) cells have been shown to possess effective cytotoxic activity against some tumor cells both in vitro and in clinical research. Furthermore, dendritic cell-activated CIK (DC-CIK) cells display significantly increased antitumor activity compared to unstimulated CIK cells. Study findings indicate DC cells can secrete chemokine C–C motif ligand 17 (CCL17) and chemokine C–C motif ligand 22 (CCL22) with a common receptor molecule, C–C chemokine receptor type-4(CCR4). CCL17 and CCL22 levels were measured by ELISA from CIK cell culture supernatants and the expression of CCR4 on CIK and DC-CIK cells was analyzed by flow cytometry. Through Migration and Killing assays, further analyzed the effects of the altered expression levels of CCR4 on the chemotactic ability and the tumor-killing efficiency of CIK cells. We found markedly increased CCL17 and CCL22 in supernatants of DC-CIK co-cultures. Similarly, the expression of CCR4 was also increased on CIK cells in these co-cultures. Further, the stimulation of CCL17 and CCL22 increased expression of the CCR4 and enhanced the migratory capacity and antitumor efficacy of CIK cells. Simultaneously, similar effects had achieved by transfecting the CCR4 gene into CIK cells. DC cells may promote the expression of CCR4 on CIK cells by secreting CCL17 and CCL22, thereby promoting infiltration of DC-CIK cells into the tumor microenvironment, and exerting stronger antitumor activity than CIK cells.